Pêcheurs artisanaux en AMP : gardiens de la biodiversité ou des frontières maritimes ? (San Andrés, Colombie) - Justine Berthod (VertigO)
From a maritime anthropology perspective, this article analyzes how artisanal fishermen of the San Andrés Archipelago are propelled to the forefront of conflicts between commoning and sea grabbing. In doing so, it questions how this contributes to document the process of the maritimization of societies. Built on six months of ethnographic work in fishing cooperatives, the article questions the positioning of artisanal fishermen as new guardians of the sea, by crossing several scales of analysis. The article first considers the recent upgrading of the social status of fishermen and then the place of their “good practices” as symbolic forms of localized appropriation of fishing territory. It then points out the contradictory dimension of the fishermen’s role of guardians of the sea at regional and sub-regional scales. In a context of regional border conflict and competitive access to oil exploration, the role assigned to fishermen by national institutions is one of heritage before being one of environmental citizens. The Biosphere Reserve fulfills above all a geopolitical function, making fishermen guardians of national frontiers rather than guardians of the biodiversity.